2014
DOI: 10.1371/journal.pone.0111031
|View full text |Cite
|
Sign up to set email alerts
|

Integration of UAV Photogrammetry and SPH Modelling of Fluids to Study Runoff on Real Terrains

Abstract: Roads can experience runoff problems due to the intense rain discharge associated to severe storms. Two advanced tools are combined to analyse the interaction of complex water flows with real terrains. UAV (Unmanned Aerial Vehicle) photogrammetry is employed to obtain accurate topographic information on small areas, typically on the order of a few hectares. The Smoothed Particle Hydrodynamics (SPH) technique is applied by means of the DualSPHysics model to compute the trajectory of the water flow during extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…), water runoff analyses (Barreiro et al. ) trash and wildlife cues. We have demonstrated that detailed surveys to map protected areas and measure trail conditions, trampling and effects on vegetation as a consequence of human use can be performed with high spatial and temporal resolution with minimal technical expertise required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), water runoff analyses (Barreiro et al. ) trash and wildlife cues. We have demonstrated that detailed surveys to map protected areas and measure trail conditions, trampling and effects on vegetation as a consequence of human use can be performed with high spatial and temporal resolution with minimal technical expertise required.…”
Section: Discussionmentioning
confidence: 99%
“…Even more, drones can be used to assess water runoff (Barreiro et al. ), erosion (Ćwiąkała et al. ) and a wide range of management relevant landscape parameters (Anderson and Gaston ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e ghost particle velocity is thought to be only related to water depth and roughness height but independent of the slope of the bed surface. Similar to the second approach [27,28], Barreiro et al [29] modified the artificial viscosity value for interactions between fluid and bottom to mimic the Manning roughness coefficient of vegetation [26]. However, there is still no universal roughness boundary of free surface flow in the current SPH framework for different flow patterns such as hydraulic smooth flow, hydraulic rough flow, or hydraulic transition flow.…”
Section: Introductionmentioning
confidence: 99%